La numérotation des cahiers et la foliotation dans les manuscrits arabes datés jusqu'à 1450 - Marie-Geneviève Guesdon (Revue des Mondes Musulmans et de la Méditerranée)
This study tries to establish a typology concerning the way in which the quires found within Arabic manuscripts were numbered ; this study is based upon manuscripts preserved in the National Library of France (BNF), which are from very different origins. The position of the indications on the page, the signs which were used (the abjad alphabet, numerals of various types, numbering written out in full letters), their content - which sometimes includes the number of the page in the quire or the tide of the work - varied over time. Some practices were followed in North Africa where the numbering of quires was less frequent whereas this appears relatively early in Christian manuscripts from the Near East - this was probably in relation to Syriac or Coptic traditions. In scientific manuscripts which originate in the Near-East and which have not been characterised as Christian, it seems that the use of the abjed alphabet and numbers was more frequent. The study of a larger number of manuscripts whose origins have been identified will allow one to further define this information.